e-GP in mechanical wing procurement in roads & highways: an assessment of efficiency - Khan, Mohammad Ali Ahmed (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.